2012
DOI: 10.1063/1.4737871
|View full text |Cite
|
Sign up to set email alerts
|

Direct physical evidence of mechanisms of leakage and equivalent oxide thickness reduction in metal-insulator-metal capacitors based on RuOx/TiOx/SrxTiyOz/TiN stacks

Abstract: Articles you may be interested inLow leakage Ru-strontium titanate-Ru metal-insulator-metal capacitors for sub-20nm technology node in dynamic random access memory Appl. Phys. Lett. Detailed leakage current analysis of metal-insulator-metal capacitors with ZrO2, ZrO2/SiO2/ZrO2, and ZrO2/Al2O3/ZrO2 as dielectric and TiN electrodes J. Vac. Sci. Technol. B 31, 01A109 (2013); 10.1116/1.4768791 Improvement in the leakage current characteristic of metal-insulator-metal capacitor by adopting RuO2 film as bottom elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“… , Earlier reports on the ALD of STO from a group at University of Helsinki have not shown promising electrical properties on such metal electrodes, and technically meaningful reports considering both points have only been made recently mostly by two groups. One is the group at Interuniversity Microelectronics Centre (IMEC), which has reported the use of Sr( t Bu 3 Cp) 2 and Ti(OMe) 4 (Bu and Me are C 4 H 9 and CH 3 , respectively) as the Sr and Ti precursors, respectively, at a low growth temperature ( T g ) of 250 °C, due to the limited thermal stability of Ti(OMe) 4 at higher T g . As already noted by the group of the present authors, STO films grown at such low T g have been accompanied by cracking problems during post deposition annealing performed to crystallize the amorphous as-deposited films . The IMEC group reported that the film is crystallized with finer grains without cracking problems when the film composition is slightly Sr-rich [Sr/(Sr + Ti) ∼ 62 atom %].…”
Section: Introductionsupporting
confidence: 64%
“… , Earlier reports on the ALD of STO from a group at University of Helsinki have not shown promising electrical properties on such metal electrodes, and technically meaningful reports considering both points have only been made recently mostly by two groups. One is the group at Interuniversity Microelectronics Centre (IMEC), which has reported the use of Sr( t Bu 3 Cp) 2 and Ti(OMe) 4 (Bu and Me are C 4 H 9 and CH 3 , respectively) as the Sr and Ti precursors, respectively, at a low growth temperature ( T g ) of 250 °C, due to the limited thermal stability of Ti(OMe) 4 at higher T g . As already noted by the group of the present authors, STO films grown at such low T g have been accompanied by cracking problems during post deposition annealing performed to crystallize the amorphous as-deposited films . The IMEC group reported that the film is crystallized with finer grains without cracking problems when the film composition is slightly Sr-rich [Sr/(Sr + Ti) ∼ 62 atom %].…”
Section: Introductionsupporting
confidence: 64%
“…This redox reaction is similar to the reported phenomenon in the SrTiO 3 based metal-oxide-semiconductor (MOS) structure. 34,35) Under the reductive atmosphere, RuO 2 is reduced to Ru and supplies oxygen to the layer, which is consistent with our results. The RuO 2 =BT-BMN structure showed less oxygen vacancies at the interface than the other electrodes.…”
Section: Resultssupporting
confidence: 92%
“…Two high-density defect distributions (N TI =3x10 20 cm -3 ), probably originated by the intermixing between the Ru electrode and the STO (28), are defined near the interfaces. A uniform defect band is also considered along the whole STO thickness (N TB =1x10 19 cm -3 ), which is due to the intrinsic concentration of O vacancies (29)(30) and it is needed to reproduce the IV curves especially at low gate voltages. Then, we run CV and IV simulations by considering the rectangular defect distributions as sketched in Fig.…”
Section: Srtio Mim Capacitorsmentioning
confidence: 99%